Komunikasi Dialogis pada Media Sosial Rumah Sakit - Arina Himatul Husna (MUKASI: Jurnal Ilmu Komunikasi, 2023)
Social media has facilitated conversations between organizations and their publics. Companies in various sectors have adopted social media for this purpose. This is also the hospitals. However, in hospital social media, information distribution has more portion than interactivity. In fact, dialogic communication is one of the factors succesfull public services. Hospitals need to present a dialogic communication dimension in communicating with their public through social media. This research presents dialogic communication carried out by hospital to interact with patients and online users on social media. The descriptive qualitative approach is considered capable of answering this question by looking at the dimensions of dialogic communication through responsiveness, conversation, active presence, interactive attitude and interactive resources. The results showed that dialogic communication was carried out by conducting online activities on social media such as uploading entertainment and educational content. Hospital also respond to incoming messages and comments on agency social media. Furthermore, hospital needs other platforms to bring sustainable and in-depth conversations.